2019
DOI: 10.5173/ceju.2019.1698
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin infusion versus third generation cephalosporin as a surgical prophylaxis for percutaneous nephrolithotomy: a randomized study

Abstract: Introduction Percutaneous nephrolithotomy (PCNL) is considered a clean-contaminated surgical procedure. The American Urological Association has recommended different preoperative antimicrobial prophylaxis for various urological procedures to prevent surgical site infections, postoperative fever, and possible sepsis. The European Association of Urology (EAU) antibiotic guidelines endorse giving either a second or third-generation cephalosporin, trimethoprim-sulfamethoxazole, fluoroquinolone or amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The miR-410 can stimulate osteogenesis and downregulate osteoclasts' production. With such a regulation, miR-410 can offer an excellent way of treating osteonecrosis ( Omar et al., 2019 ) . Dai et al.…”
Section: Therapeutic Role Of Mirna In Several Bone Diseasesmentioning
confidence: 99%
“…The miR-410 can stimulate osteogenesis and downregulate osteoclasts' production. With such a regulation, miR-410 can offer an excellent way of treating osteonecrosis ( Omar et al., 2019 ) . Dai et al.…”
Section: Therapeutic Role Of Mirna In Several Bone Diseasesmentioning
confidence: 99%
“…A total of 831 studies were identified for potential inclusion in the meta-analysis. After a fulltext review, 10 articles were identified as relevant for this study and selected for inclusion in the meta-analysis (Fig 1) [4,5,[9][10][11][12][13][14][15][16].…”
Section: Eligible Studiesmentioning
confidence: 99%
“…The characteristics of the 10 included studies are shown in Table 1 [4,5,[9][10][11][12][13][14][15][16]. These comparative studies described patients who underwent antibiotic prophylaxis for PCNL for renal stones.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations